The art of governing local education markets – municipalities and school choice in Finland. Issue 2 (3rd April 2019) - Varjo, Janne; Kalalahti, Mira
ABSTRACT: Since the 1980s, numerous education reforms in Europe and beyond have sought to dismantle centralised bureaucracies and replace them with devolved systems of schooling that emphasise parental choice and competition between diversified types of schools. Despite this general trend, Finland continues to emphasise the municipal assignment of school places, albeit with the possibility of locally controlled choice. The aim of this paper is to elaborate on the ways in which Finnish local education authorities – involving both officials and politicians – define themselves in relation to the changing conceptions of the Nordic welfare state model. The paper discusses the social costs and benefits of school choice in addition to the kinds of techniques these authorities use when aiming to control and manage the social costs and benefits of school choice. Based on nine in-depth thematic interviews with local education authorities, the modalities – having to, being-able, wanting and knowing how – will be analysed.